Enhancement of the optical response in a biodegradable polymer/azo-dye film by the addition of carbon nanotubes - Díaz Costanzo, Guadalupe (2014)
A new biodegradable photoresponsive material was developed using poly(lactic acid) (PLA) as the matrix material and Disperse Orange 3 (DO3) as photoisomerizable azo-dye. It was observed that the addition of multi-walled carbon nanotubes (MWCNTs) leads to a new phenomenon consisting of an enhancement of the optical anisotropy in a wide range of temperatures. In particular, the optical anisotropy increases 100% at room temperature. Moreover, the material containing MWCNTs shows a faster optical response that is evidenced as an increase in the growth rate of optical anisotropy. Spectroscopic data is provided to study the interaction among DO3, MWCNTs and PLA. The enhancement of optical anisotropy obtained with the addition of MWCNTs was related to the glass transition temperature (Tg) of each material. Maximum optical anisotropy was obtained 15 °C below the Tg for both materials. Results are interpreted in terms of the interactions among DO3, MWCNTs and PLA and the packing density of the dye into the polymer chains.